Economy of environment - current science with traditions - Korporowicz, Violetta (Studia Ecologiae et Bioethicae, 2003)
The fact that problems of environmental degradation and its protection are getting more important is caused among others by limitations in management efficiency. It forces us to look at economic processes with consideration of the output of such disciplines that say how one shall manage in a situation of limited natural resources. This discipline is without any doubt environmental protection. This science indicates methods and economic instruments that can be applied in economic practice necessary in environmental protection. It deals also with problems related to economic researches of implications of environmental policy. The same environmental economics that results from the neo-classical trend of economics looking at the market as an unfailing mechanism of economic regulation proves that the invisible hand of the market fails in the case of environmental protection. That is why we shall apply different types of instruments especially these related to indirect regulation (including such economic instruments as taxes) that support actions related to the limitation of environmental degradation. It's worth also adding that recognition of methodological premises of this science supports not only the development of this discipline but first of all, it shows her applicable character. Practical usage of rules prepared by environmental economics shall be used by all participants of economic life beginning with consumers and finishing with producers and governing in order to keep not only current natural resources but first of all to take care after possible development of the next generations.